Features of the Principle of Universal Suffrage and for Mass Political Participation of Citizens: Foreign Experience - Irina Sergeevna Alekhina (Управленческое консультирование)
The article is devoted to the implementation of the principle of universal suffrage, qualification limiting the implementation of the principle of universality, lessons learned in the implementation of the principle of developed and developing countries, as well as a variety of policy research to improve the electoral activity of citizens and, accordingly, to involve society in the management process.